2023
DOI: 10.1002/csr.2538
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and consequences of corporate social responsibility decoupling—Status quo and limitations of recent empirical quantitative research

Abstract: This study reviews recent empirical quantitative research on firm‐ and country‐related determinants of corporate social responsibility (CSR) decoupling and the consequences on firm value. Based on legitimacy theory and agency theory, top managers use CSR decoupling for self‐impression management and stakeholder attraction. Our review indicates that low (high) corporate governance quality increases (decreases) CSR decoupling and it has negative financial consequences for firms. We identify major research gaps a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…It should be noted that companies' efforts to practice CSR have a significant relationship with enhancing the legitimacy of corporate actions. This is highlighted by the emergence of legitimacy theory in this field, which has been extensively utilized in research studies [107][108][109][110]. It should be noted that some studies, such as [111], reported that legitimacy theory is considered one of the most important applicable theories regarding directing environmental practices and activities.…”
Section: Social Clustermentioning
confidence: 99%
“…It should be noted that companies' efforts to practice CSR have a significant relationship with enhancing the legitimacy of corporate actions. This is highlighted by the emergence of legitimacy theory in this field, which has been extensively utilized in research studies [107][108][109][110]. It should be noted that some studies, such as [111], reported that legitimacy theory is considered one of the most important applicable theories regarding directing environmental practices and activities.…”
Section: Social Clustermentioning
confidence: 99%
“…In [108], the focus was on open innovation and the triple bottom line for sustainability. While [135] examined the role of institutional dynamics in CSR performance, [139] reviewed empirical studies on the determinants of CSR decoupling and its consequences. In [140], the nexuses between CSR adoption, business strategies and governance were explored.…”
Section: Gaps and New Research Directionsmentioning
confidence: 99%
“…In general, the higher the level of corporate governance, the less corporate CSRD behavior. Once the enterprise has CSRD behavior, it will have a negative impact on the financial performance (Velte P, 2023) [4]. The better the CSR performance, the higher the financial performance, and the better CSR performance is related to the improved information transparency (Shang & Fu, 2024) [5].…”
Section: Consequences Of the Corporate Csrdmentioning
confidence: 99%